The here and now - Brashares, Ann (Delacorte Press, 2014)
Seventeen-year-old Prenna, an immigrant who moved to New York when she was twelve, came from another time and she and the other travelers must follow strict rules to avoid destroying the new life they have worked so hard to get, as well as the one person Prenna is desperate to protect.